Tekanan emosi remaja Islam - Fariza Md. Sham, (Penerbit Universiti Kebangsaan Malaysia, 2005)
A stressed society exhibits the attitudes of being aggressive, anxiety, and hasty rage. The stressed society too is grief-stricken and is vulnerable to mental disorder, which eventually leads them to commit suicide. Islamic mission approach is considered to be a kind of social support that can help adolescents with emotional stress. Therefore, this study which has been administered on adolescents in Kajang, Selangor Darul Ehsan, is aimed at ascertaining whether adolescents have stress based on symptoms of stress which comprise of psychological, physiological and behavioral aspects. Besides, this study also is to find factors leading to stress and how adolescents manage stress either in positive or negative manner. To achieve this objective, an analysis was carried out on 403 respondents consisted of male and female adolescents ranging from 16 -17 years old. Data were collected through questionnaires and structured interviews. Data analysis was carried out based on descriptive statistic approach and it is shown in forms of timetable and chart with brief explanations of frequency and percentage. The result of the study indicates that adolescents do have emotional stress, whereby most of them showing the psychological symptoms of stress. The result also reveals that the factors leading to it are family and environmental problems. As far as the aspect of solving the problem is concerned, most of the adolescents studied resort to positive ways of solving their problems